Human Spermatogenesis Tolerates Massive Size Reduction of the Pseudoautosomal Region. (12th August 2020) - Fukami, Maki; Fujisawa, Yasuko; Ono, Hiroyuki; Jinno, Tomoko; Ogata, Tsutomu
Abstract: Mammalian male meiosis requires homologous recombination between the X and Y chromosomes. In humans, such recombination occurs exclusively in the short arm pseudoautosomal region (PAR1) of 2.699 Mb in size. Although it is known that complete deletion of PAR1 causes spermatogenic arrest, no studies have addressed to what extent male meiosis tolerates PAR1 size reduction. Here, we report two families in which PAR1 partial deletions were transmitted from fathers to their offspring. Cytogenetic analyses revealed that a ∼400-kb segment at the centromeric end of PAR1, which accounts for only 14.8% of normal PAR1 and 0.26% and 0.68% of the X and Y chromosomes, respectively, is sufficient to mediate sex chromosomal recombination during spermatogenesis. These results highlight the extreme recombinogenic activity of human PAR1. Our data, in conjunction with previous findings from animal studies, indicate that the minimal size requirement of mammalian PARs to maintain male fertility is fairly small.